Could molecular variations be predictive in right and left colon cancer in different gender and age groups? - Hatice Cilem Solak; Nazli Mert; Asim Leblebici; Zerrin Isik; Ender Berat Ellidokuz; Yasemin Basbinar (PLoS ONE, 2026)
Background Left-sided colon-cancer (LCC) and right-sided colon cancer (RCC) harbor different clinical entities and different therapy protocols. Our study aimed to demonstrate genomic expression differences and clarify the clinical differences between LCC and RCC by using in-silico methods. Methods Our study compares mRNA expression levels between clinical groups to describe variations in molecular characteristics between right-left-sided colon cancer (216 right-141 left) using the TCGA-COAD database. We identified differentially expressed genes and analyzed survival profiles for RCC and LCC. We applied a gene set enrichment analysis and merged the results by group to highlight common and different pathways. Results The results reveal that TG, INSL5, EREG and AIRE were found as age-related genes, and TG, INSL5, EREG, AIRE, HOXB8 and FLT3 were found as gender-related genes for RCC and LCC. We found that high expression of the AIRE gene was linked with poor survival in patients with RCC in males and under 65 age groups. High expression of LEP was correlated with poor survival in patients with RCC, regardless of gender. In addition, low expression of the EREG gene was linked with poor survival in women with RCC. Conclusions Three genes (AIRE, LEP, EREG), which are effective on the EGFR pathway, would have great predictive and prognostic importance in the context of anti-EGFR therapies.